New proposed fractional-polynomial functions: new recommendation for overcome the imbalance in three-phase systems - Q. S. Vu; Bui Vu Minh; Minh Tran; N.V. Korovkin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Non-linear loads or load imbalances, etc., are the typical causes of asymmetric operation of three-phase systems. The appearance of inverse (positive) and homopolar (zero) symmetric components cause damage to the systems and electrical equipment and increase the power losses on the transmission lines. Reactive power compensation is one of the solutions that can overcome this asymmetry. The difficulty that exists in many different methods is the optimal calculation of the value of the compensator. In this paper, a new method to overcome these problems is proposed and investigagted. The proposed method is based on the fundamental electrical quantities (voltages and currents) on the controllable values of the static compensation devices and overcoming of the asymmetric operation regime in the three-phase systems.